2018
DOI: 10.1016/j.ssmph.2018.07.002
|View full text |Cite|
|
Sign up to set email alerts
|

Weighed down by discriminatory policing: Perceived unfair treatment and black-white disparities in waist circumference

Abstract: Police maltreatment, whether experienced personally or indirectly through one’s family or friends, represents a potentially harmful stressor, particularly for minority populations. We address this issue by investigating: (1) how waist circumference (WC) varies by personal and vicarious exposure to unfair treatment by police (UTBP); and (2) to what extent exposure to UTBP explains the black-white disparity in WC. We employed data collected from a community-based sample of black (n = 601) and white (n = 608) adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 43 publications
(53 reference statements)
1
34
0
Order By: Relevance
“…Negative police interactions with the public have been well documented through the media, but research on the personal and vicarious affects have been limited. One study by McFarland et al. (2018) demonstrated that negative police interactions personally or vicariously experienced cause harm and stress, which is correlated to obesity and increased waist circumference and is a debilitating burden on Black individuals ( Boyd, 2018 ; McFarland et al., 2018 ).…”
Section: Main Textmentioning
confidence: 99%
“…Negative police interactions with the public have been well documented through the media, but research on the personal and vicarious affects have been limited. One study by McFarland et al. (2018) demonstrated that negative police interactions personally or vicariously experienced cause harm and stress, which is correlated to obesity and increased waist circumference and is a debilitating burden on Black individuals ( Boyd, 2018 ; McFarland et al., 2018 ).…”
Section: Main Textmentioning
confidence: 99%
“…2014; Jones 2014; Kerrison and Sewell 2020; McFarland et al. 2018; Sewell 2017; Sewell and Jefferson 2016). They set the background upon which new threats to health lean into inequitably‐produced vulnerabilities revealing the social costs of infection from pathogens such as covid‐19.…”
Section: Paradoxes Of Pandemics and Policingmentioning
confidence: 99%
“…He makes sure not to break into a run as he paces with sheer excitement at the thought of playing with his gaming buddies from across the world—an excitement that distracts him at school to the point that he isoftenrelegated to detention. He is always aware of the probability of policing—aggressive, unnecessary, and frequent (Boyd et al 2019; Brunson 2007; MacDonald et al 2007; McFarland et al 2019; Weitzer and Tuch 2014).…”
Section: One Block One Woman One Lifementioning
confidence: 99%
See 2 more Smart Citations